Actividades extracurriculares y su influencia en el aumento del rendimiento escolar en los estudiantes de séptimo año de educación básica de la Unidad Educativa “María Andrea” del cantón Babahoyo, Provincia de Los Ríos - Chica Tuárez, Gilbert Vinicio (2019)
The extended school day is a topic that is being discussed as a solution to improve academic performance, whose ultimate goal is to make countries more competitive in the global economy, where policies to lengthen the school day have become increasingly most popular in recent decades. The reason is simple: more time in class should result in better learning. In the Maria Andrea Educational Unit, it is intended to encourage extracurricular activities so that children after the school day, display their interests and promote their abilities beyond the traditional school curriculum, offering the students of this Educational Unit a space safe and supervised to explore interests, learn new skills and spend valuable time with adults and people of the same age. The purpose of this research is to publicize the benefits of extracurricular activities by connecting teaching through the home, the community and the classroom. The content of the program, the members of the team and even the location help determine if the program will be successful and attractive.